KTSP dan Materi Sastra Beberapa Catatan - Sunu Wasono (HISKI, 2007)
This paper discusses literary material and textbooks in relation to the implementation of the Kurikulum Tingkat Satuan Pendidikan (KTSP). There are three issues that need to be underlined: First, KTSP gives schools an opportunity to design their own curriculums. Secondly, KTSP must be supported by textbooks such as literary anthologies. Finally, the standard of competence and basic competence stipulated by the BNSP should not be used as the only reference in curriculum design since the curriculum itself is not without any weaknesses.